Computer Based Learning and Laboratory Based Learning in Electric Circuits: A Literature Review - Aballe, Kathy Sheen; Tabago, Roe Francis; De Juan, Earl John; Suganob, Aida Lou; Cardaño, Milkay Mae; Pederiso, Angeline; Mercado, Justine C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Computer based learning and laboratory-based learning are widely used nowadays mainly for teaching and learning of both teacher and students especially in teaching electrical circuits. This paper aims to review computer-based learning and laboratory-based learning, specifically other forms of CBL and LBL and how these methods are integrated in teaching and learning electrical circuits, and its advantages and disadvantages. In conducting this literature review, the researchers adapted the PRISMA method in which various journal articles are screened through different stages. Criterion was imposed to guide the researchers in the inclusion and exclusion process. It was found out that there are other forms of computer-based learning (CBL) such as the Java-based virtual laboratory and Grid computing laboratory. Also, integrating computer-based learning and laboratory-based learning would build a workable environment that helped in motivating students in exploring electrical circuits. There are various advantages of computer-based learning such as time saving and easy access to laboratory manuals. On the other hand, advantages of laboratory-based learning include the positive impact of interaction, group discussion, and collaboration that was delimited by the computer-based learning.